McGraw-Hill encyclopedia of science and technology; Vol.1: AAR - AOR (An international reference work in twenty volumes including an index) (New York, 1997)
This Encyclopedia presents pertinent information in every field of modern science and technology. The 7.100 article titles are alphabetically sequenced, so that often the reader can quickly find information by choosing from 19 text volumes that one bearing the appropriate letter for the subject
Keywords: science - encyclopedias,technology - encyclopedias